THE ROLE OF THE HEADMASTER IN IMPLEMENTING MANAGEMENT EDUCATION IN THE SCHOOL ENVIRONMENT - Bahdin Nur Tanjung (Universitas Negeri Medan, 2023)
The purpose of research on the role of school principals in building education management is to gain a deeper understanding of the role of school principals in leading, organizing and directing education management activities in schools. Research methodology Library Research Management (LRM) is a type of research methodology used in research in the field of education management. LRM emphasizes the use of library resources as a data source in research. The role of the principal is very important in building good educational management in the school environment. The principal as the main leader in the school is responsible for developing appropriate strategies and policies to improve the quality of education in his school. In building effective education management, school principals must be able to understand their roles and responsibilities, and have sufficient managerial skills to manage existing resources in schools.